Genome-Wide Analysis on Transcriptome and Methylome in Prevention of Mammary Tumor Induced by Early Life Combined Botanicals - Itika Arora; Shizhao Li; Michael R. Crowley; Yuanyuan Li; Trygve O. Tollefsbol (Cells, 2022)
Breast cancer (BC) is the most common malignancy and the second leading cause of cancer death among women in the United States. The consumption of natural dietary components such as broccoli sprouts (BSp) and green tea polyphenols (GTPs) has demonstrated exciting potential in reducing the risk of BC through the regulation of epigenetic mechanisms. However, little is known about their impacts on reversing epigenomic aberrations that are centrally involved in the initiation and progression of BC. Previously, we have determined the efficacy of combined BSp and GTPs treatment on the inhibition of the growth of a mammary tumor in a transgenic Her2/neu mouse model. We sought to extend our previous study to identify universal biomarkers that represent common mechanistic changes among different mouse models in response to this dietary regime by including a new transgenic mouse model, C3(1)-SV40 TAg (SV40). As a result, we identified novel target genes that were differentially expressed and methylated in response to dietary botanicals when administered singly (BSp and GTPs) and in combination (BSp + GTPs) in both mouse models. We discovered more differentially expressed and methylated genes in the combination treatment group compared to the singly administered groups. Subsequently, several biological pathways related to epigenetic regulations were identified in response to the combination treatment. Furthermore, when compared to the BSp and GTPs treatment alone, the combinatorial treatment showed a more significant impact on the regulation of the epigenetic modifier activities involved in DNA methylation and histone modifications. Our study provides key insights about the impact of the combined administration of BSp and GTPs on BC using a multi-omics analysis, suggesting a combinatorial approach is more efficacious in preventing and inhibiting BC by impacting key tumor-related genes at transcriptomic and methylomic levels. Our findings could be further extrapolated as a comprehensive source for understanding the epigenetic modifications that are associated with the effects of these dietary botanicals on BC prevention.